PENGARUH BUDAYA DIGITAL DAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN TERHADAP KINERJA PEGAWAI DI KANTOR KSOP KELAS I PANJANG - Ali Martopo; Faurani I Santi Singagerda (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of Digital Culture and Employee Information Systems on Employee Performance at KSOP Kelas I Panjang. The research problem is the digital gap among employees, which causes some employees to lag behind in utilizing technology-based systems. This study uses a quantitative approach with a survey method, where data were collected through questionnaires from 101 respondents selected using saturated sampling. The data analysis technique is carried out using multiple linear regression with the assistance of SPSS version 26.0 statistical software. The research results show that partially, digital culture has a positive and significant effect on employee performance. Furthermore, the Employee Information System (SIM Kepegawaian) has a positive and significant effect on the performance of KSOP Kelas I Panjang employees. Simultaneous testing results indicate that Digital Culture and the Employee Information System have a positive and significant effect on the performance of KSOP Kelas I Panjang employees. These findings suggest that when the digital culture is strong and the personnel information system is easy to use and beneficial, the level of technology acceptance among employees becomes high, thereby directly impacting performance improvement.